Nazwy własne Ziemi Lubuskiej jako przedmiot badań zielonogórskich językoznawców = Proper names of the Lubuskie Region as the object of research by linguists from Zielona Gora - Żuraszek-Ryś, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper aims to assess the scope of research conducted by linguists from Zielona Gora regarding proper names in the Lubuskie Region. The research material comprises works authored by Polish studies scholars affiliated with the University of Zielona Gora, whether as permanent or temporary staff; in the latter case, only those contributions made during employment at the university are considered. The findings reveal that proper names in the Lubuskie Region have consistently been a significant focus for Zielona Gora linguists, particularly in one area of onomastics, i.e., toponymy.
Keywords: onomastyka; toponimia; chrematonimia; antroponimia; onomastyka literacka; poprawność nazw własnych; badania zielonogórskich językoznawców; onomastics; toponymy; chrematonymy; anthroponymy; literary onomastics; proper name correctness; research by Zielona Gora linguists